Relationship between Perceived Parenting Style and Social Adjustment: A Study of Secondary School Students of Haryana - Jaglan , Sushila (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
The upbringing of a child is the most delicate, crucial responsibility of a parent. While routine parental responsibilities like feeding, providing for and educating a child can somewhat be taken for granted, the molding of personality and character is truly the prime duty of any parent. People often say that a child is a reflection of the effort and dedication of the parents. Student in the age group of 12-16 years stepped into the new world wherein social acceptable behavior is the desired norm of the home, neighborhood and the society. In other words, students have to be socially adjusted in the prevailing society. Those, who are not always, bear the brunt of the members of the society. They are generally called maladjusted, delinquent, not fit for society, not one among us. Therefore, it is very important for the students to know from this age what acceptable behaviour is and how one has to harmoniously adjust to the surroundings. Parents once again has the key role in making the child more socially adjusted to his surrounding by shaping and reinforcing the behavior which are acceptable. Therefore, in this study the researcher tries to investigate what kind of relationship parenting style shares with social adjustment of the students.